Queen Square - John Wood the Elder
The earliest of urban facades was built in 1728 in Georgian Bath as part of a speculative development for the society which left London during the hot and unsanitary summer months and gathered in Bath. This fashion had begun early in the eighteenth century, but with the building of places such as this, grew to a peak by 1790 and brought with it an unprecedented demand for domestic architecture on an urban scale. The originator John Wood (1704-53), later wrote that he put his houses "under a regular front, as a sample for uniting several houses so as to have the outside appearance of one magnificent structure." Nothing like it had been seen before in Northern Europe, except for J.H. Mansart's circular Place des Victoires in Paris, built in 1686. The building seen here is, in fact, seven private houses, each planned according to the needs of its original owners, combined under one Palladian front.